Use of rapeseed and pea grain protein supplements for organic milk production - Khalili, H.; Kuusela, E.; Saarisalo, E.M.; Suvitie, M. (1999)
In experiment 1 a duplicated 4 X 4 Latin square design was used in which 8 Finnish Ayrshire cows in mid-lactation were given 8 kg of oats and barley and grass/red clover silage ad libitum with or without (controls) commercial rapeseed meal (218 g/kg DM; RSM), crushed organic field pea (Pisum sativum L.) (452 g/kg DM; P) or a mixture of pea (321 g kg DM) and organic rapeseed (Brassica rapa L. oleifera subannua) (155 g/kg DM; PRS). Cows on P and PRS diets produced as much milk as cows on the RSM diet. Milk yield was higher but protein content lower with PRS diet than with diet P (P<less than>0.05). In experiment 2 a triplicated 3 X 3 Latin square design was used in which 9 cows were given 8 kg of a mixture of: (1) 395 g/kg oats, 395 g/kg barley and 210 g/kg commercial heat-moisture treated rapeseed cake (RSC); (2) (ORSC) consisted (g kg<sup(<minus>1)>) of 375 g/kg oats, 375 g/kg barley and 250 g/kg cold-pressed organic rapeseed cake (ORSC); or (3) 395 g/kg oats, 395 g/kg barley and 250 g/kg commercial heat-moisture treated rapeseed cake with additional rapeseed oil (0.38 kg) (RSCO). There was no dietary effect on the yield of energy-corrected milk. Milk yield was higher with RSCO diet than the other diets (P<less than>0.05).